PENGARUH PENAMBAHAN CaCO3 DAN WAKTU PENYIMPANAN TERHADAP KADAR VITAMIN C PADA PROSES PENGHAMBATAN PEMATANGAN BUAH TOMAT (Lycopersicum esculentum Mill) - Rudi Kartika (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2010)
The aim of this research is to know the influence of CaCO3 addition and storage duration to vitamine C concentrate in ripe obstruction process of tomato (Lycopersicum esculentum Mill). Calcium carbonate(CaCO3) which is added 0; 0.2; 0.4; 0.6 and 0.8 percent of weight and storage duration were 0; 2; 4; 6; 8; 10 and 12 days. Vitamine C was determined by using iodometric titration method. The data obtained were then analized by ANOVA test and LSD test. The result showed that CaCO3 addition could influence vitamine C concentrate in ripe obstruction process of tomato (Lycopersicum esculentum Mill) on standard 5% and 1% with Ftest > Ftabel (5% and 1%) or F(7.6667) > F(2.50 and 3.60) and storage duration could influence vitamine C concentrate in ripe obstruction process of tomato (Lycopersicum esculentum Mill) on standard 5% and 1% with Ftest > Ftabel (5% and 1%) or F(1204.2222) > F(2.32 and 3.07). Based on the result LSD test on significant standard 5% (0.0143) and 1% (0.0190), optimum vitamine C concentrate were 0.8589 mg/10 g on 0.2% of calcium carbonate (CaCO3) addition and 10 days of storage duration.Keywords : ANOVA, CaCO3, LSD, tomato, vitamine C, storage duration